Chemical composition of ‘Kiaat’ (Pteropcarpus angolensis) bark and the effect of herb pastes on the quality changes in marinated cat fish during chilled storage - B. O. T Ifesan, B. A. Origbemisoye (Food Biology, 2019)
Kiaat (Pterocarpus angolensis) bark, which is valued for its high medicinal effects, was subjected to proximate analysis, while the extract from its bark was examined for, phytochemicals and minerals compositions. Kiaat bark was mixed with garlic, to preserve minced fresh catfish and was stored at 4 oC for 9 days. Physical and chemical characteristics were analysed. The results of proximate composition revealed that kiaat bark contains high crude fibre (30.67%), protein (17.33%) and low contents of fat (2.98%). Phytochemical screening showed that the kiaat bark has flavonoid (1.90%), tannin (5.79%) alkaloid (2.96%) and phenol (5.90%) contents. The mineral determination revealed that kiaat bark contained high calcium (24.50 mg/100g), iron (17.20 mg/100g) content with very small amount of lead (0.01 mg/100g). The pH (6.30) of the minced cat fish marinated with kiaat bark+garlic at day 0 tends to be more acidic with increase in storage days and was 4.80 at day 9. The total volatile nitrogen values (TVB) (0.30 mg/100 g-5.46 mg/100 g) were lower than the standard limit (<35 mg/100 g sample). Trimethylamine in minced fish preserved with kiaat paste+garlic was 0.36 mgN/100g which later decreased to 0.16 mgN/100g at day 9, while values for samples with only kiaat bark and the control ranged from 0.64 mgN/100g -0.8 mgN/100g at day 9. Results further showed that thiobarbituric acid reactive substances (TBARs) values raised in all marinated samples during storage, especially in control sample (2.1-5.0 mgma\100g), sample with kiaat paste (0.2-4.2mgma100g) and fish treated with kiaat paste+garlic (0.24-3.67mgma\100g). Addition of garlic to kiaat bark paste may be a preffered method to increase shelf-life of fresh catfish during chilled storage.